Australia and New Zealand Islet and Pancreas Transplant Registry Annual Report 2018—Islet Donations, Islet Isolations, and Islet Transplants. Issue 2 (February 2019) - Webster, Angela C.; Hedley, James A.; Anderson, Patricia F.; Hawthorne, Wayne J.; Radford, Toni; Drogemuller, Chris; Rogers, Natasha; Goodman, David; Lee, Melissa H.; Loudovaris, Thomas; Kelly, Patrick J.
Abstract : Background: This is an excerpt from chapter 4 of the annual registry report from the Australia and New Zealand islet and pancreas transplant registry. The full report is available athttp://anziptr.org/reports/ . Methods: We report data for all allogeneic islet isolation and transplant activity from 2002 to end 2017. Solid organ pancreas transplantation activity is reported separately. New Zealand does not have an islet transplant program. Data analysis was performed using Stata software version 14 (StataCorp, College Station, TX). Results: From 2002 to 2017, a total of 104 allogeneic islet transplants were performed in 62 recipients. Conclusions: The number of islet transplants performed in Australia was slightly lower in 2017 but continues to increase over time.